The Impact Of Motivation, Empowerment, Organizational Culture On Organizational Commitment With Leader-Member Exchange As Mediator - Rashidah, Mohamad Ibrahim; Albataneih Othman, Hussein Mefleh (2017)
Jordanian municipalities' play an important role in advancing economic developments as well as nurturing the well-being of its populace. Thus, it is vital that the issue of organizational commitment must be embedded among the municipalities workforce so that the objectives to serve the community for the betterment of its populace can be achieved. Committed employees are more productive and efficient worker and would less likely to leave from their organization. This is because these employees are willing to sacrifice their time, effort and energy to achieve the organization’s goal in serving the ever demanding public needs. In addition, motivation, empowerment and organizational culture also play antecedent role in enhancing commitment among the workforce. If commitment among workforce is low, the public as the end user will suffer since the workforce will perform badly such as absenteeism, corruption, misuse of power, delay in approvals that can be detrimental to the municipalities’ images as the engine of growth for its community. Hence, public complaints shall be accumulating and shall portray negative image for the municipalities. Therefore, the objective of this paper is to investigate the relationship between motivation, empowerment and organizational culture towards organizational commitment and whether leader-member exchange has the mediating impact on the relationship. The population for this study is the municipalities’ workforce throughout Jordan. It is expected that the findings will reveal positive associations among these variables and with the inclusion of leader-member exchange as the mediating factor shall further enhance the organizational commitment among the Jordanian municipalities workforce.